2011
DOI: 10.1177/030857591103500404
|View full text |Cite
|
Sign up to set email alerts
|

‘Me and My Child’: Parenting Experiences of Young Mothers Leaving Care

Abstract: Previous research suggests that a woman's past experiences of being parented will have a significant influence on how she parents her own children. This study, reported by Amanda Maxwell, Julie Proctor and Linda Hammond, aimed to explore young care-leaving mothers' experiences of motherhood, focusing on their experience of themselves as mothers, their relationship with their child and their understanding of their child's experiences. Six mothers were interviewed who had spent time in care and were teenagers at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…Pregnancy generated hope for the future (Chase et al, 2009;Schwerdtfeger & Wampler, 2009;Pryce & Samuels, 2010;O"Mahen et al, 2011). The responsibility of pregnancy was seen in a positive light, stimulating self-caring and protective behaviour (Armstrong & Pooley, 2005;Chase et al, 2009;Maxwell, Proctor & Hammond, 2011). Pregnancy was also seen by some women as an opportunity to receive love, suggesting a, perhaps sadly misplaced, hope that the baby might meet some of the mothers" own emotional needs.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy generated hope for the future (Chase et al, 2009;Schwerdtfeger & Wampler, 2009;Pryce & Samuels, 2010;O"Mahen et al, 2011). The responsibility of pregnancy was seen in a positive light, stimulating self-caring and protective behaviour (Armstrong & Pooley, 2005;Chase et al, 2009;Maxwell, Proctor & Hammond, 2011). Pregnancy was also seen by some women as an opportunity to receive love, suggesting a, perhaps sadly misplaced, hope that the baby might meet some of the mothers" own emotional needs.…”
Section: Discussionmentioning
confidence: 99%
“…This research outlines the personal vulnerabilities and structural challenges faced by this group, 147,149,150 but also notes some more positive aspects of parenthood. Becoming a mother was reported as presenting an opportunity 'to set "right" the 'wrong of their past' 151 in terms of both young people's own family history and in motivating them to stabilise their lifestyle and circumstances. 152 Having a child of their own was for many women the first time they could develop a relationship offering a sense of permanency and in a family in which 'their value and membership could not be questioned'.…”
mentioning
confidence: 99%
“…149 In contrast to their childhood experiences, young mothers said they hoped to be an 'ideal' good parent, although found the LOOKED-AFTER CHILDREN NESTED STUDY NIHR Journals Library www.journalslibrary.nihr.ac.uk reality to be challenging and sometimes overwhelmingly demanding, expressing self-doubt about their competence. 151 Studies reported women's mistrust of social services and resulting reluctance to seek professional support. 151,152 However, in general, motherhood was described as rewarding and 'an opportunity for healing and renewal', 153 despite also putting these women at increased risk.…”
mentioning
confidence: 99%
See 2 more Smart Citations